Establishing patterns of structural-phase transformations when processing technogenic waste of high-speed steels by carbon thermal reduction - Rebenko, Victor; Lukianenko, Ivan; Volokh, Vadym; Andreev, Andrey; Poliakov, Anatolii; Yamshinskij, Mykhail; Zhuravel, Dmytro; Ivanchenko, Dmytro; Kovalenko, Iryna; Chaplyhin, Yevhen (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is structural and phase transformations during the reduction of high-speed steel scale with carbon to obtain a resource-saving alloying additive. The task addressed is the loss of high-value elements when obtaining and using alloying material from man-made raw materials. Solving the problem is associated with determining technological indicators to enable the reduction of losses of the corresponding elements. It has been determined that the phase composition of the scale had the manifestation of FeO, Fe2O3, Fe3O4, FeWO4, MoO2, FeW3C, W2C and Mo2C. In the reduction products, a solid solution of alloying elements and carbon in α-Fe, residual oxides Fe2O3, Fe3O4 and carbides FeW3C, WC, Mo2C, Cr7C3, Cr3C2, Cr23C6, VC was found. The disordered structure of the scale with particles of irregular shape after reduction was characterized by the presence of formations of polyhedral and rounded shapes with different contents of alloying elements. Residual oxygen was within 5.78–7.14% by weight. It was established that achieving a reduction degree of 79% is sufficient since the residual carbon in carbides provides an increased reducing ability during the further reduction of the oxide component in the liquid metal during alloying. The porous structure causes faster dissolution compared to standard ferroalloys, which reduces the resources consumed by reducing the melting time. No phases with an increased tendency to sublimation were found in the obtained alloying additive. That is, there is no need to create additional conditions that prevent the loss of alloying elements during evaporation with the gas phase, which ensures an increase in the degree of extraction of the corresponding elements. The properties of the obtained alloying additive allow it to be used in smelting in an electric arc furnace as a replacement for part of standard ferroalloys